Anacroneuria iporanga (Plecoptera: Perlidae): description of the nymph and biological notes - De Almeida, Lucas Henrique [UNESP]; Cardoso-Leite, Ricardo; Boa Deodato, Mariana Fonte; Bispo, Pitagoras Da Conceicao [UNESP] (Magnolia Press, 2019)
The Neotropical stonefly genus Anacroneuria (Perlidae) is represented by approximately 80 species in Brazil, but the nymphs of only 11 of these species have been associated and described. In this paper, we describe the previously unknown nymph of A. iporanga from Intervales State Park, Sao Paulo State, Brazil and present biological observations for this species
Keywords: Aquatic insects; stoneflies; immatures; lotic environments